Classical modelling of the effect of heterogeneity on reservoir performance of Agbada formation (2015)
Understanding the basic mechanisms that govern flow of hydrocarbon in any given reservoir situation is necessary in developing reliable methods of predicting behaviour in that reservoir. Most reservoirs in Agbada Formation of the Niger Delta Basin are anisotropic and therefore heterogeneous, which is a vital parameter in the efficient production of hydrocarbons. This work looked at the effect of permeability anisotropy (Kv/Kh) or heterogeneous distribution and its effects on reservoir performance using windows based IPM-MBAL petroleum engineering software. Results analysis revealed that anisotropy makes reservoir production modelling more realistic than the isotropic scenarios, and degree of heterogeneity improves oil recovery from the reservoir (Kv/Kh = 1, R.F = 49.31%; Kv/Kh = 0.1, R.F = 49.95%; Kv/Kh = 0.001, R.F = 50.60%; Kv/Kh = 0.0001, R.F = 51.24%). Reservoir heterogeneity should be included in reservoir modelling practices because it has a significant effect on hydrocarbon production.